The cobalt oxidation state in preferential CO oxidation on CoOx/Pt(111) investigated by operando X-ray photoemission spectroscopy. Issue 16 (7th April 2022) - Rattigan, Eoghan; Sun, Zhaozong; Gallo, Tamires; Nino, Miguel Angel; Parreiras, Sofia de Oliveira; Martín-Fuentes, Cristina; Martin-Romano, Juan Carlos; Écija, David; Escudero, Carlos; Villar, Ignacio; Rodríguez-Fernández, Jonathan; Lauritsen, Jeppe V.
Abstract : Ambient pressure XPS study of cobalt oxide on Pt(111) catalysts links Co oxidation state with activity in preferential CO oxidation. Abstract : The combination of a reducible transition metal oxide and a noble metal such as Pt often leads to active low-temperature catalysts for the preferential oxidation of CO in excess H2 gas (PROX reaction). While CO oxidation has been investigated for such systems in model studies, the added influence of hydrogen gas, representative of PROX, remains less explored. Herein, we use ambient pressure scanning tunneling microscopy and ambient pressure X-ray photoelectron spectroscopy on a CoO x /Pt(111) planar model catalyst to analyze the active phase and the adsorbed species at the CoO x /Pt(111) interface under atmospheres of CO and O2 with a varying partial pressure of H2 gas. By following the evolution of the Co oxidation state as the catalyst is brought to a reaction temperature of above 150 °C, we determine that the active state is characterized by the transformation from planar CoO with Co in the 2+ state to a mixed Co 2+ /Co 3+ phase at the temperature where CO2 production is first observed. Furthermore, our spectroscopy observations of the surface species suggest a reaction pathway for CO oxidation, proceeding from CO exclusively adsorbed on Co 2+ sites reacting with the lattice O from the oxide. Under steady state CO oxidation conditions (CO/O2 ), the mixed oxide phase is replenished from oxygen incorporating into cobalt oxide nanoislands. In CO/O2 /H2, however, the onset of the active Co 2+ /Co 3+ phase formation is surprisingly sensitive to the H2 pressure, which we explain by the formation of several possible hydroxylated intermediate phases that expose both Co 2+ and Co 3+ . This variation, however, has no influence on the temperature where CO oxidation is observed. Our study points to the general importance of a dynamic reducibility window of cobalt oxide, which is influenced by hydroxylation, and the bonding strength of CO to the reduced oxide phase as important parameters for the activity of the system.